Rabbi Abraham Ibn Ezra's commentary on Books 3-5 of Psalms, chapters 73-150 - Ibn Ezra, Abraham ben Meïr, 1089-1164 (Touro College Press ; Academic Studies Press, 2016)
Rabbi Abraham ibn Ezra's commentary is one of the great biblical exegeses produced by medieval Jewry. His commentary accompanies almost every version of the Rabbinic Bible, and his influence on biblical studies continues to this very day. Ibn Ezra sought to provide the literal meaning of the biblical text. However, he did more than that. His commentary is saturated with insights into Hebrew grammar, medieval philosophy, and astrology. Rabbi Abraham ibn Ezra's Commentary on Books 3-5 of Psalms: Chapters 73-150 completes the publication of the translation and annotation of Ibn Ezra's commentary to Psalms, making it available to both scholars and general readers.
Keywords: Bible. -- Psalms -- Commentaries -- Early works to 1800.; Bible. -- Psalms; RELIGION -- Biblical Studies -- Old Testament.; RELIGION -- Biblical Studies -- Wisdom Literature.; Commentaries; Early works